Determinar la calidad de carne bovina mediante medicion de ph y acidez en tercenas de la ciudad de Zaruma - Gualán Namcela, Cecilia Verónica (2017)
This work is carried out with the help of a digital ph meter for the measurement of the pH of beef. It consists of measuring pH minutes after the slaughter in the slaughterhouse until it goes on the market. Then, the respective samples were taken in 5 butchery meat shops in the town of Zaruma, of which: two meat shops have a proper handling of beef; the other two meat shops do not have a very proper handling of beef, and the last shop which has improper handling of beef. The samples are taken in the morning, in the afternoon and in the morning of the following day, with the purpose of getting the different values of pH in the beef in its different stages and with the different handling of each meat shop. This is due to the fact that beef changes some indicators when exposed to the environment, one of which is the pH (taking in consideration that there are some factors that interfere, like the post mortem condition of the bovine, the time of storage in the meat shops, and how refrigeration is managed). An alive muscle’s pH is close to neutrality, but when the bovine’s death occurs after 24 hours of sacrifice the pH value found is close to that of 5.5, which is considered an optimal average indicating that beef is in good quality. This value varies because it depends on the storage management carried out in each meat shop. Therefore, the purpose of measuring the pH of bovine beef is to know and evaluate the quality of beef sold in the city of Zaruma, since consumers could by simple observation assume that meat is in good state, but not actually know if it is fit for consumption. Many times the adequate quality control is not performed and bad meats are sold to consumers, sometimes causing harm upon consumption. Much of this mismanagement occurs because the people who sell in meat shops are unaware of how meat storage must be handled. In some meat shops meat is exposed to the environment for a few days without refrigeration until they sell it all, and in other meat shops the beef is not refrigerated but rather frozen and taken out it as its’ sold. Only a few of the meat shops have the right refrigeration management in order for it to reach its point of maturation, with proper color and texture. It is for this reason that the present study focuses on trying to get variable values and demonstrate that the improper handling of beef has resulted in the selling and exposure of bad quality meat to the public.